HUBUNGAN ORKIDEKTOMI DAN DETORSI DENGAN RESPON IMUN TESTIS KONTRALATERAL PADA TORSIO TESTIS - Ongkorahardjo, Edwin; Hardjowijoto, Sunaryo; Soetojo, Soetojo (Indonesian Journal of Urology, 2008)
Objective: In attempt to explain effects of orchiectomy and detorsion in contralateral testis immune response after unilateral testicular torsion. Materials and methods: Forty eight rattus norwegicus strain wistar white rats testes underwent 720º unilateral left testicular torsion. The experimental animals were divided into 6 group: 2 had sham operation which served as control, 2 groups had ligation left testicular torsion with subsequent orchiectomy at 4 and 24 hours, 2 groups had ligation left testicular torsion followed by detorsion at 4 and 24 hours. Contralateral testes were analyzed 7 days later for examination percentage of IL-4 producing lymphocyte and immunoglobulin G producing plasma cells in contralateral testis by means of immunohistochemical method. Results: Multivariate analysis result revealed that in unilateral left testicular torsion followed by detorsion at 24 hours group we found IL-4 and IgG had entered intratubules and were different from orchiectomy and control group (p=0,0001 and p=0,0001). This indicated damage of germinal epithelium in contralateral testes caused by imunologic response stimulated by detorsion. In left testicular torsion and orchiectomy or detorsion at 4 hours did not show both IL-4 and IgG in intratubules and no significant different both IL-4 and IgG in extratubules among orchiectomy, detorsion and control group (p=0,326 and p=0,064). This indicated that in 4 hours immune response were not significantly different between those groups and germinal epithelium were still intact. Conclusion: Detorsion in 24 hours testicular torsion had stimulated immune response which caused damage of germinal epithelium in contralateral testis. In 4 hours testicular torsion immune response happened not significantly different between detorsion, orchiectomy and control.